Experimental study of the shot peening treatment effect on austenitic stainless steel. (2016) - Chaib, Mohammed; Megueni, Abdelkader; Ziadi, Abdelkader; Guagliano, Mario; Belzunce, Francisco Javier Varela
Surface treatments are increasingly used to enhance fatigue resistance of metal parts by improving the properties of the surface layer of materials. The aim of this study is to highlight the effect of shot peening on the surface state of an austenitic stainless steel, both in terms of surface work hardening and as regards the residual stress field. An extensive experimental work by means of X-ray diffraction, micro hardness and microscopy observation allowed to assess that shot peening is also able to generate a nanostructured layer of material. An analytical equation was defined to relate the treatment parameters and its main effect based on the experimental results with the aim to provide a useful tool for a correct design of the shot peening treatment.